Alcohol use in the Pacific region: Results from the STEPwise approach to surveillance, Global School‐Based Student Health Survey and Youth Risk Behavior Surveillance System. (10th September 2015) - Kessaram, Tara; McKenzie, Jeanie; Girin, Natalie; Roth, Adam; Vivili, Paula; Williams, Gail; Hoy, Damian
Abstract: Introduction and Aims: Alcohol use is a leading risk factor for disease and injury in Pacific Island countries and territories (PICT). This paper examines drinking patterns across 20 PICTs. Design and Methods: We synthesised published data from the STEPwise approach to surveillance or similar surveys for adults 25–64 years, and from the Global School‐Based Student Health surveys and Youth Risk Behavior Surveillance System (YRBSS) for youth. We examined current and heavy drinking, and for adults also frequency of consumption. Using YRBSS, we studied trends in youth alcohol use in US‐affiliated PICTs between 2001 and 2013. Results: Alcohol consumption in adults and youth varied considerably across PICTs. In eight PICT populations, over 60% of male adults were current drinkers. Male adults consumed alcohol more frequently and engaged in heavy drinking more than female adults. Similar gender differences occurred in current and heavy drinking among youth. Across 10 PICTs, current drinking prevalence in males 13–15 years ranged from 10% to over 40%. Declines in alcohol use among grade 9–12 students were observed in YRBSS, although the magnitude differed by island and sex. Discussion and Conclusions: Alcohol consumption varies widely between PICTs. There are marked gender differences in use and abstention. There is scope in PICTs for implementation of best practice strategies to reduce alcohol‐related harm. These need to be gender responsive and cognisant of concerning patterns of youth drinking. Strengthening surveillance of alcohol use and its consequences is vital to inform and monitor the impact of national and regional policies. [Kessaram T, McKenzie J, Girin N, Roth A, Vivili P, Williams G, Hoy D. Alcohol use in the Pacific region: Results from the STEPwise approach to surveillance, Global School‐Based Student Health Survey and Youth Risk Behavior Surveillance System. Drug Alcohol Rev 2016;35:412–423]